Analysis of Family Knowledge about Health Diet and Nutritional Status among The Elderly - Pertiwi, Gracia Herni; Sastrini, Yovita Erin; Jiu, Cau Kim; Ariyanti, Sri (Universitas Padjadjaran, 2026)
The increasing number of elderly people has an impact on the increase in specific problems that occur in the elderly, one of which is nutritional problems. An important aspect that families must have is adequate knowledge in preparing balance nutritional needs. If nutritional needs are not met in a balanced manner, health problems can occur in the elderly. Diseases or health problems among the elderly can lead them to limit their food intake, thereby worsening their condition. Restricting food due to dietary restrictions imposed by their condition will lead to a lack of nutrients the body needs. This study aims to determine families’ knowledge about healthy diets and nutritional, status in the elderly This research method used a descriptive-analytic design with a cross-sectional approach. The study population consisted of families with elderly members aged ≥ 55 years who voluntarily participated. The sample included families who accompanied or lived with the elderly. The respondents’ ages ranged from ≥ 26 years, and a total of 57 families with elderly members aged ≥ 55 years or older voluntarily participated in this study. The analysis in this study used univariate analysis to determine the frequency distribution and bivariate analysis using the Chi-Square test. The analysis was conducted for each family knowledge category and the Mini Nutritional Assessment (MNA). Based on the distribution of family knowledge about healthy diets, 39 respondent were in the good category, 33 respondent had a normal nutritional status. Family is also an important factor in the lives of the elderly. Statistical analysis results show that there is a relationship between family knowledge about healthy diets and nutritional status fulfillment in the elderly. The results of this study indicate that there is a correlation between the level of knowledge possessed by families and the nutritional status of elderly individuals. Families with sufficient knowledge are able to provide meals that take into account the types of food, frequency of meals, and daily menus for elderly individuals in order to maintain their nutritional status within the good or normal range.